Study on the Regional Innovation Network of Pearl River Delta City Cluster and Its Factor Analysis - Kong, Jiyu (International Journal of Global Economics and Management, 2023)
The Pearl River Delta (PRD) city cluster is a national key development area with favorable geographical conditions, and the construction of a regional innovation network will help enhance the economic vitality of the region and the corresponding comprehensive competitiveness, and the PRD city cluster is accelerating the construction of an international science and technology innovation center with global influence. The purpose of this paper is to study the innovation network of the PRD city cluster and to explore the key factors of the regional innovation network using factor analysis. The study proposes the main components of the regional innovation network of the Pearl River Delta city cluster, analyzes them by factor analysis, and finally puts forward suggestions or recommendations.